Modeling the assessment of the connection of migration and economic development: Case of Azerbaijan - Bayramov, Shahin V.; Muradov, Rashad S.; Efendiyev, Rufat J.; Hajiyeva, Leyla A.; Aliyev, Elnur S. (Journal of Eastern European and Central Asian Research (JEECAR), 2021)
The article's purpose was to model the assessment of the associated impact of migration and economic of Azerbaijan. The indicators of the correlation between the intensity of migration and economic growth have been substantiated. Using the Granger test, the cause-and-effect relationships of migration and the country's economic development were determined. Based on the identified relationships, a polymodal complex has been built, consisting of regression models, which reflect the nature of the mutual influence between socio-economic development indicators and the intensity of migration in Azerbaijan. The hands' number of immigrants and emigrants in Azerbaijan for 2024 has been predicted considering the impact of the COVID-19 pandemic. The optimal ratio between the number of immigrants and emigrants was determined by linear optimization, ensuring GDP per capita in Azerbaijan at the level of modern economic development. The results obtained can serve as a basis for the development of a compelling state migration policy.